The enduring field: Exploring researcher emotions in covert research with antagonistic organisations. Issue 2 (7th June 2018) - Maguire, Heather; McCartan, Andrew; Nash, Catherine Jean; Browne, Kath
Abstract : This paper explores the emotional dimensions of doing covert research with antagonistic organisations. Drawing on the experiences of three researchers who identify as lesbian, gay, and LGBT ally, who covertly attended public and semi‐public conferences and events organised by groups with heteroactivist positionings over two years, we consider the multiple, nuanced and complex emotional dimensions of being "behind enemy lines" (Jansson, 2010 ). We argue for greater consideration of the emotional spaces covert research creates, as in our case a "closet" space was produced which suppressed our sexualities or allyship. Furthermore, we argue that the process of doing covert research is one that both precedes and exceeds being in the field, and as such, we need to pay attention to researcher emotion as a process that begins long before we step into the field and continues long after we leave.